THE TRANSPARENCY AND ACCOUNTABILITY EFFECT OF EDUCATION MANAGEMENT ON STUDENT PARENTS PARTICIPATION IN JAKARTA PUBLIC SENIOR HIGH SCHOOL NO. 107 - Eli Solihat; Toto Sugiharto (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The objectives of the present study are to analyze the effect of transparencies and accountabilities of education management on level of participation of parents of students at SMA Negeri 107 Jakarta. Stratified random sampling was performed to select 87 respondents from the study population (i.e., 693 parents of students at SMA Negeri 107 Jakarta). Data concerning perceptions of respondents towards transparencies and accountability of education management as well as their willingness to participate in education management at the school were collected from respondents using a set of valid and reliable questionnaires. Multiple linear regression analysis wasapplied to analyze the data. It is concluded that transparencies and accountabilities of education management partially and simultaneously affect participation of parents of students.Key words: transparency; accountability; participation of students’ parents; education management.